The future role of intermediaries: a study on Malaysian travel agencies / Mohd. Mokhtar Mohd. Ghani … [et.al.] - Mohd. Ghani, Mohd. Mokhtar; Raja Abdul, Raja Mazhatul Yasmin Suraya; Muzaffar Shah, Malek (2007)
This paper reports an investigation of the Malaysian conventional travel agencies in facing the reality growth of Internet and e-business technology. Realizing the threats of “disintermediation", this study explores the awareness level of the agencies in perceiving their role as middlemen in a digital marketplace. Based on 250 samples selected among the ticketing agencies in Malaysia, 124 of them have responded to the survey. The findings illustrate, despite the fact that Internet based e-business technology adoption is still at limited stage, the perception level of the technology usage remain positive in enhancing their business performance. To be totally eliminated by the technology is not their main concern. Their role is seen as a main contributor towards the growth of the Malaysian travel industry and hence, e-business will continuously bring them an opportunity to evolve and innovate as an intermediary in the near future.